1996
DOI: 10.1095/biolreprod54.5.1103
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cells are Widely Distributed in Murine Fetuses in Utero1

Abstract: Passage of maternal cells into conceptuses in utero is recognized but poorly defined in species with hemochorial placentation. Despite the potential importance for such a phenomenon in vertical disease transmission, only limited data address the frequency of material to fetal cell trafficking or the developmental stage of its initiation. A murine model system, involving transfer of LacZ-, scid/scid, or wild type (+/+) blastocysts to pseudo-pregnant, LacZ+ transgenic ROSA26 females provided both flow cytometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 28 publications
2
60
2
2
Order By: Relevance
“…To explore the mechanism of maternal stem cell transmission to conceptuses in utero, we delivered cells intravenously at E17 and assessed fetal organs collected at E21, as well as 3-12 weeks after delivery. Marleau et al [7] reported maternal cells first appearing in fetal thymus at E12.5, coincident with the maturation of the hemochorial interface [1]. Morphologically heterogeneous maternal cells were present predominantly in bone marrow and thymus in more than 90% of late-gestation fetuses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To explore the mechanism of maternal stem cell transmission to conceptuses in utero, we delivered cells intravenously at E17 and assessed fetal organs collected at E21, as well as 3-12 weeks after delivery. Marleau et al [7] reported maternal cells first appearing in fetal thymus at E12.5, coincident with the maturation of the hemochorial interface [1]. Morphologically heterogeneous maternal cells were present predominantly in bone marrow and thymus in more than 90% of late-gestation fetuses.…”
Section: Discussionmentioning
confidence: 97%
“…Placenta is not an absolute barrier: cells can pass from mother to fetus and vice versa [1][2][3][4]. Maternal cells have been demonstrated in fetal circulation [5] and in liver, spleen, thymus, thyroid, and skin of neonatal organs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although it could be argued that these findings reflect maternal to fetus trafficking during labor, other studies indicate that transfer occurs in the course of gestation because maternal DNA has been reported in fetal blood from second and third trimester pregnancy terminations (4,5). In experimental studies, maternal cells were found in the marrow cavities of developing bones in immune-competent mice (6).…”
Section: Maternal Cells Have Recently Been Found In the Circulation Amentioning
confidence: 98%
“…(Forni et al, 1988). This may indicate that much of the force driving development of the immune system is derived from exposure to alloantigens encountered in utero (Claas et al, 1988;Piotrowski and Croy, 1996) rather than postnatal exposure to pathogens. Unfortunately, in the study of Forni et al (1988), T helper cell differentiation was not assessed, and therefore it is not known whether memory T helper cell numbers increase in absence of xenogeneic challenge.…”
Section: Leukocytes In Blood and Spleen During Developmentmentioning
confidence: 99%